Моделирование характеристик тандемного монолитного солнечного элемента Si/Ge с буферным слоем Si1–хGeх - Гниленко, А.Б.; Лаврич, Ю.Н.; Плаксин, С.В. (Технология и конструирование в электронной аппаратуре, 2015)
Проведено компьютерное моделирование тандемного монолитного солнечного элемента Si/Ge с буферным слоем Si1–хGeх, получены вольт-амперные характеристики, рассчитаны фотовольтаические параметры и найдено распределение основных физических величин. Показано, что добавление второго германиевого каскада позволяет существенно повысить коэффициент полезного действия кремниевых фотоэлектрических преобразователей. Проведено комп'ютерне моделювання тандемного монолітного сонячного елемента Si/Ge з буферним шаром Si1–хGeх, одержано вольт-амперні характеристики, розраховано фотовольтаїчні параметри і знайдено розподіл основних фізичних величин. Показано, що додатковий германієвий каскад дозволяє суттєво підвищити коефіцієнт корисної дії кремнієвих фотоелектричних перетворювачів. Excitation of bulk and surface acoustic waves with the interdigital transducer (IDT), which is deposited on the surface of piezoelectric crystal, is widely used in the development of devices in acoustoelectronics and in the design of the microwave acousto-optic deflectors. Excitation of bulk acoustic waves by IDT in the devices on surface acoustic waves leads to the appearance of spurious signals. At the same time excitation of bulk acoustic waves with IDT from the surface of lithium niobate crystals allows creating high frequency acousto-optic deflectors, which makes possible to significantly simplify the technology of their production. Therefore, significant attention is paid to the task of excitation and distribution of bulk acoustic waves with IDT including recent times by the method of simulation of their excitation and distribution. The obtained theoretical results require experimental verification.